Ultrasound assessment of subglottic region for estimation of appropriate endotracheal tube size in pediatric anesthesia - Pughal Vendan Gnanaprakasam; Venkatesh Selvaraj (Wolters Kluwer Medknow Publications, 2017)
Background and Aims: Endotracheal tube (ETT) selection in pediatric patients is mainly done with the age, height, or weight-based formula. We compared ultrasound assessment of the subglottic area to predict the outer diameter of the ETT, with that of modified Cole's formula. The aim of the study is to compare the appropriateness of uncuffed ETT selection based on modified Cole's formula with that of ultrasound assessment method of subglottic diameter in children undergoing surgical procedures under general anesthesia. Material and Methods: This is a prospective, randomized, parallel group study. One hundred and fifty American Society of Anesthesiologists I and II patients of age 2-6 years were randomly allotted into two groups: Group A - ETT selection based on ultrasound assessment of subglottic diameter. Group B - ETT selection based on modified Cole's formula. The study parameters are the internal diameter and external diameter (OD) of the predicted ETT by the two methods and that of the appropriate size ETT used. Results: The incidence of appropriate tube selection was 74.7% in the ultrasound based group while it was 45.3% in the modified Cole's formula group. There was a strong correlation between OD of the optimal ETT used and the ultrasound assessed subglottic diameter. Bland-Altman analysis of OD of appropriately sized ETT and subglottic diameter by ultrasound assessment has a bias of 0.02 mm with limits of agreement of +1.78 to −1.74. Conclusion: Ultrasonographic assessment of the subglottic diameter at the cricoid region is a better tool in predicting the appropriate size uncuffed ETT than modified Cole's formula.